2016
DOI: 10.1002/ajmg.a.37775
|View full text |Cite
|
Sign up to set email alerts
|

Etiologies of uterine malformations

Abstract: Ranging from aplastic uterus (including Mayer-Rokitansky-Kuster-Hauser syndrome) to incomplete septate uterus, uterine malformations as a group are relatively frequent in the general population. Specific causes remain largely unknown. Although most occurrences ostensibly seem sporadic, familial recurrences have been observed, which strongly implicate genetic factors. Through the study of animal models, human syndromes, and structural chromosomal variation, several candidate genes have been proposed and subsequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 266 publications
0
42
0
2
Order By: Relevance
“…In one such example, it has been found that müllerian anomalies coexist in higher rates among monozygotic twins compared with dizygotic twins with a 12-fold increase in risk among first-degree relatives 1 4. Genes that have been implicated in this wide possibility of abnormalities include HNF1B, HOX genes and WNT pathways 1. The extragenital system most strongly associated with müllerian anomalies is the renal system, including urogenital dysplasia and hypoplasia of the urogenital ridge 1–3.…”
Section: Discussionmentioning
confidence: 99%
“…In one such example, it has been found that müllerian anomalies coexist in higher rates among monozygotic twins compared with dizygotic twins with a 12-fold increase in risk among first-degree relatives 1 4. Genes that have been implicated in this wide possibility of abnormalities include HNF1B, HOX genes and WNT pathways 1. The extragenital system most strongly associated with müllerian anomalies is the renal system, including urogenital dysplasia and hypoplasia of the urogenital ridge 1–3.…”
Section: Discussionmentioning
confidence: 99%
“…A longitudinal vaginal septum is associated with 75% of these anomalies and no communication is present between the two endometrial cavities and the two horns [2] [3] [4] [5]. The remaining MDAs include: Class I-vaginal agenesis, Class II-unicornuate, Class IV-bicornuate, Class V-septate, and Class VI-arcuate.…”
Section: Introductionmentioning
confidence: 99%
“…Müllerian ducts give rise to the following structures: fallopian tubes, uterus, the cervix, and the proximal two thirds of the vagina [3]. MDAs are multifactorial, resulting from a spectrum of improper development, fusion, canalization, or reabsorption of the Müllerian ducts between 6 and 20 weeks gestation [3] [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Syndromes in which hypoplastic/aplastic uterus is part of the clinical presentation. Modified from(38).…”
mentioning
confidence: 99%